MODEL IN READING COMPREHGENSION AT FIFTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT STATE ISLAMIC UNIVERSITY SULTHAN THAHA SAIFUDDIN JAMBI - Wardatun, Sisi Ulya (JR-ELT (Journal of Research in English Language Teaching), 2021)
This research aims to find out and analyze the models used by students in reading comprehension. This research was conducted in semester V, majoring in English education, The State Islamic University of Sulthan Thaha Saifuddin Jambi. Which is located at JL. Jambi Ma. Bulian KM.16 Duren River Intersection, Kab. Ma.Jambi. Researcher used descriptive qualitative methods, and found the models used by students when reading or when being interviewed. The subjects in this study were class B, totaling 28 students, which focused on 6 students to be interviewed. Research methods of data collection using observation, documentation, and interviews. When, in the interview, the researcher found answers based on the formulation of the problem. Researcher found a model that is often used by students when understanding reading. This study uses two models in reading comprehension, first the Top-Down Model and the second Bottom-Up Model. In this study, the model most often used by students when understanding a text is the Top-Down model, while the one that is least used is the Bottom-Up Model. The top-down model can be concluded that the reader's knowledge, experience, and intelligence are needed as a basis for reading comprehension. The bottom-up model is a process that involves accuracy, detail, and identification of letters, words, spelling patterns, and other language units